Seasonal activity and unpredicted polar front migration of northern New Zealand Common Diving Petrels (Pelecanoides urinatrix). (3rd July 2017) - Rayner, Matt J.; Taylor, Graeme A.; Gaskin, Chris P.; Dunphy, Brendon J.
ABSTRACT: The Common Diving Petrel ( Pelecanoides urinatrix ) is an abundant seabird species within New Zealand waters. Breeding in this species occurs from late July through to December and adults are thought to remain in New Zealand waters during non-breeding months. Yet no studies of the spatial ecology of the species within New Zealand have been undertaken to confirm this. We used geolocation loggers with seawater immersion probes to characterise the year-round distribution and activity of P. urinatrix from two colonies (Kauwahaia Island and Burgess Island) in northern New Zealand. Adult birds exhibited extended pre-laying occupation of breeding sites (~95 days) and throughout breeding remained within 300 km of their colony. Burgess Island birds returned near nightly to their burrows throughout the breeding season. During non-breeding birds made a rapid and unpredicted migration south-east to the Antarctic polar front (covering 3000–5000 km in 3–13 days) and exhibited a dramatic shift in behaviour by spending 95% of their time on (and under) the water surface. Given its already high wing loading, it appears that the primary moult reduced flight efficiency during this time. But by targeting highly productive oceanic regions, and the improved foraging opportunities therein, P. urinatrix may offset this reduced flight capacity.